Penggunaan Kutipan Amos 9:11-12 dalam Kisah Para Rasul 15:18-20 sebagai Lensa Misional - Anon Dwi Saputro (Sekolah Tinggi Teologi Kalimantan, 2023)
The interpretation of the quotation of Amos 9:11–12 in Acts 15:18–20 encounters several issues both on the theological and practical sides. In the study, the author uses an intertextual approach to examine the two texts. The missional lens relates to the quotation of Amos 9:11–12 that James used to quell the disputes in Jerusalem. The quote opens the horizon of thinking about the mission of the church. The article aims to find the meaning of the use of Amos 9:11–12 in Acts 15:18–20 from a missional perspective. The results of this study revealed the meaning contained in the quotation of Amos 9:11–12 used by James in Acts 15:18-20 from a missional perspective. The quotation of Amos 9:11-12 is the basic key to the development of Paul's missional theme to both Jews and Gentiles in Acts and provides a correct perspective from a theological and practical perspective. In conclusion, the use of Amos 9:11-12 in Acts 15:18–20 can be seen as a missional lens that provides a broader view of the church's mission and its duties. It reminds the church to always seek God's will, respect the history and traditions of the church, and rebuild fellowships that have fallen apart or been marginalized. With this broader view, the church can perform its mission more effectively and continue to thrive as a fellowship of believers in Jesus Christ.Tafsiran mengenai kutipan Amos 9:11-12 dalam Kisah Para Rasul 15:18-20 mengalami beberapa masalah baik dalam sisi teologi maupun sisi praktis. Dalam pengkajiannya, penulis menggunakan pendekatan intertekstual untuk menelaah kedua teks tersebut. Lensa misional berkaitan dengan kutipan Amos 9:11-12 yang digunakan Yakobus untuk meredam perselisihan di Yerusalem. Kutipan tersebut membuka cakrawala berpikir tentang misi gereja. Artikel bertujuan untuk menemukan makna dari penggunaan Amos 9:11-12 dalam Kisah Para Rasul 15:18-20 dalam perspektif misional. Hasil penelitian ini menemukan makna yang terkandung kutipan Amos 9:11-12 yang digunakan Yakobus dalam Kisah Para Rasul 15:18-20 dari perspektif misional. Kutipan Amos 9:11-12 merupakan kunci dasar pengembangan tema misional Paulus baik kepada orang Yahudi ataupun non Yahudi dalam Kisah Para Rasul serta memberikan perspektif yang benar dari sisi teologis dan praktis. Dalam kesimpulannya, penggunaan kutipan Amos 9:11-12 dalam Kisah Para Rasul 15:18-20 dapat dipandang sebagai sebuah lensa misional yang memberikan pandangan yang lebih luas tentang misi gereja dan tugasnya. Kutipan ini mengingatkan gereja untuk selalu mencari kehendak Allah, menghormati sejarah dan tradisi gereja, dan membangun kembali persekutuan yang telah runtuh atau terpinggirkan. Dengan pandangan yang lebih luas ini, gereja dapat melakukan misinya dengan lebih efektif dan terus berkembang sebagai persekutuan orang percaya dalam Yesus Kristus.